2017
DOI: 10.1101/216846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory Figure-Ground Segregation is Impaired by High Visual Load

Abstract: Figure-ground segregation is fundamental to listening in complex acoustic environments. An ongoing debate pertains to whether segregation requires attention or is ‘automatic’ and pre-attentive. In this magnetoencephalography (MEG) study we tested a prediction derived from Load Theory of attention1 that segregation requires attention, but can benefit from the automatic allocation of any ‘leftover’ capacity under low load. Complex auditory scenes were modelled with Stochastic Figure Ground stimuli (SFG2) which o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…in several studies (Molloy, Lavie, & Chait, 2019;O'Sullivan, Shamma, & Lalor, 2015). We 568 suggest that the deficit here is in fundamental auditory segmentation that affects multiple 569 auditory cognitive domains based on the demonstrated lesion in auditory cortex.…”
Section: Segregation Impairment At a Fundamental Level 527mentioning
confidence: 77%
“…in several studies (Molloy, Lavie, & Chait, 2019;O'Sullivan, Shamma, & Lalor, 2015). We 568 suggest that the deficit here is in fundamental auditory segmentation that affects multiple 569 auditory cognitive domains based on the demonstrated lesion in auditory cortex.…”
Section: Segregation Impairment At a Fundamental Level 527mentioning
confidence: 77%
“…Accordingly, if it is assumed that 40‐Hz ASSRs comprise an overlap of wave V from the brainstem and MLR (in line with the superposition hypothesis), the ASSRs in the present research did not differ with load and task because we recorded responses that happen before the filtering occurred. However, because primary auditory cortex is the main generator of 40‐Hz ASSRs (Brugge et al, 2009; Engelien, 2000; Gutschalk, 1999; Herdman, 2002; Pantev, 1996; Ross, Miyazaki, & Fujioka, 2012), this explanation would be inconsistent with findings that load affects activations related to figure‐ground segregation in the auditory cortex, as measured with magnetoencephalography (Molloy, Lavie, & Chait, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…This was interpreted as indicating that high visual load reduced the gain on early auditory responses by depleting resources critical for auditory sensory processing. Molloy et al [11] (see also [12]) further showed that high load can severely impair computations associated with auditory figure-ground segregation, with effects observed from the earliest stages of processing in auditory cortex (see also [13]). Overall, these results point to the fact that what we may commonly consider as inherently auditory processes [14,15] actually draw on general computational capacity such that they can be affected by visual perceptual load.…”
mentioning
confidence: 96%
“…Brain imaging can overcome this challenge by recording brain responses to ignored and entirely task irrelevant stimuli while participants are fully engaged in a primary task. Emerging evidence indeed demonstrates that visual load can affect auditory processing from relatively early cortical (but likely not subcortical; see [8]) processing stages [9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation